THE EFFECTIVENESS OF THE VILLAGE INFORMATION SYSTEM IN THE REALIZATION OF E-GOVERNMENT - Hanum, Fiqriyah; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the effectiveness of the Village Information System (SID) in realizing e-government in Sumokali Village, Candi District, Sidoarjo Regency, by emphasizing the accuracy of program targets, socialization, objectives, and monitoring as explained in the theory of effectiveness by Budiani. Method: The research uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation, as well as data analysis following the Miles and Huberman model. Results: The results of the study show that SID has been targeted at the village community as recipients of information, but its use has not been evenly distributed due to differences in digital literacy. Socialization is still limited through WhatsApp groups so that it does not reach all residents, while the program's goals have not been fully achieved because the system has not been optimally managed and the community relies more on unofficial social media. Program monitoring is carried out through visit traffic and village evaluation forums, but it is still administrative and has not touched the quality of utilization. Overall, the effectiveness of SID in Sumokali Village has not been optimal. Novelty: These findings confirm that the success of e-government implementation at the village level is not only determined by the existence of a digital system, but also the readiness of human resources, digital literacy, and local institutional support, so this study makes a new contribution to examining the practical obstacles to SID implementation at the village level.